2013
DOI: 10.1177/1744629513511355
|View full text |Cite
|
Sign up to set email alerts
|

Students’ attitudes towards individuals with an intellectual disability

Abstract: The aim of the study was to investigate attitudes held by a British student population towards individuals with an intellectual disability. Students participated in focus groups addressing their attitudes, behaviours and perceptions of individuals with an intellectual disability. Thematic analysis was the method used to identify emergent themes. Results identified five main themes in relation to intellectual disabilities. The themes suggest that attitude scales fail to effectively measure the multidimensional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…The evidence for an established theme was arrived at by the triangulation of codes, frequency of occurrences, and interview quotes (Hodgetts et al, 2013, p.168). The authors reviewed all themes for reliability; these were then reassessed and confirmed by the co-coder (Patel & Rose, 2014). The involvement of both authors and co-coder during each stage of the data analysis allowed for triangulation and peer checking (Brantlinger, Jimenez, Klinger, Pugach, & Richardson, 2005).…”
mentioning
confidence: 99%
“…The evidence for an established theme was arrived at by the triangulation of codes, frequency of occurrences, and interview quotes (Hodgetts et al, 2013, p.168). The authors reviewed all themes for reliability; these were then reassessed and confirmed by the co-coder (Patel & Rose, 2014). The involvement of both authors and co-coder during each stage of the data analysis allowed for triangulation and peer checking (Brantlinger, Jimenez, Klinger, Pugach, & Richardson, 2005).…”
mentioning
confidence: 99%
“…The evidence of an established theme was arrived at by triangulation of codes, frequency of occurrences, and interview quotes (Hodgetts et al). The author reviewed all themes for reliability; these were then reassessed and confirmed by the co-coder and author (Patel & Rose, 2014). The involvement of author and cocoder in each stage of the data analysis enabled triangulation and peer checking (Patel & Rose).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research suggests that there is confusion amongst students as to what an ID is (Patel & Rose, ). Participants were therefore presented with a definition of an ID for reference throughout the study, to ensure that the questionnaire was completed with an accurate knowledge of what IDs are, in order to maintain construct validity.…”
Section: Methodsmentioning
confidence: 99%